Estudo químico-quântico do empilhamento π entre uma quinazolina livre e o complexo cis-[Ru(bpy)2(qui)NO](PF6)3 e sua influência sobre a fotoquímica e fotofísica deste complexo - Tiago, Fernanda de Souza (2011)
In this work, we performed quantum-chemical studies, based on the use of Density Functional Theory (DFT) and its time-dependent version (TD-DFT), of the nitrosyl ruthenium complex cis-[Ru(bpy)2(qui)NO](PF6)3.(qui), known to release NO under the action of visible light. The studies were based on experimental evidence available (Fornari, 2009). In order to confirm the occurrence of π stacking and therefore the most likely structure for the complex, calculations were made for the cation cis-[Ru (bpy)2(qui)NO]3+(qui). Additionally, we studied the role of the quinazoline ligand outside the coordination sphere in phenomena related to the thermodynamic stability of the complex, and aspects of their photophysics and photochemistry, specifically related to the photorelease of NO. The strategy used to search for the best conformation is based on the rigid scan of strategic points, using the uncoordinated quinazoline as a probe, by varying the distance between this quinazoline and certain positions in the complex, as well as dihedral angle. With the generated potential energy surfaces, it was possible to infer the most probable position of the uncoordinated quinazoline with respect to the cation complex. From the most likely structure, obtained from the surfaces generated by the rigid scan, optimization and frequency calculations were made aiming to determine the structure of minimum energy in water and in other eleven different solvents, in which there are previous experimental data. Having the optimized structure for cis-[Ru (bpy)2(qui)NO]3+(qui), the H1 RMN and UV-VIS spectra were simulated, varying atomic basis sets and functional, used in the search of the condition of best match with experimental results. Thus, the structure of the complex ion with π stacking was determined as well as the influence of the non-coordinated quinazoline in the photorelease of NO, which occurs through a charge transfer process. In this work, we present a safe, efficient and computationally feasible method, to treat weak interactions in complex, allowing its application to other systems of interest.